Desenvolvimento cognitivo e linguístico de crianças em sofrimento psíquico nos dois primeiros anos de vida - Silva, Maria Fernanda Almeida (2018)
Considering child development as founded in the early years of life in the biological conditions of the baby and in the emergence of its psyche, both in its psychic structural dimension, in the Freudo-Lacanian sense, and in terms of the birth of intelligence (CORIAT, JERUSALINSKY, 1996) , this research thematizes the relationship between psychic suffering and cognitive and linguistic development. In this interpretation, a qualitative-quantitative research was elaborated, in which the objectives were to analyze the psychic constitution and suffering of a group of infants from 0 to 24 months and the possible relations of this suffering with the cognitive and linguistic development of these infants evaluated by Bayley III (Bayley, 2006) at the age of 18 and 24 months. It also sought to analyze the concordance between the psychic risk in the first 18 months, detected by the Clinical Indicators / Risk for Child Development (IRDI), and the 18 and 24 months risk detected by the Modified Checklist for Autism in Toddlers (M-CHAT). These objectives were investigated in a first cohort study that included the application of these scripts and instruments in 20 infants and their relatives in a health unit in the city of Santa Maria. The family members also answered a questionnaire on socio-demographic, psychosocial and obstetric aspects. As a result, a statistically significant correlation was found between language impairment in Bayley III and M-CHAT at 18 months, it was observed that children with psychic risk in the first eighteen months, evaluated by the IRDI, presented lower performance in the Bayley III test, both in the cognitive and linguistic aspects, although there was no statistically significant correlation, and that the presence of risk in IRDI was not always accompanied by a presence of risk in M- CHAT, aiming at the specificity of this test for autism. In the second study, we sought to deepen the discussion of the relationship between the results observed in the psychic risk and the results observed in the cognitive and language evaluation in the study of two cases that included the visualization and analysis of filming of the interaction of mothers and babies by two psychologists. The judges evaluated the play in their cognitive, linguistic and affective dimension based on the script developed for the research, and these results were confronted with the history of each baby collected in the cohort study, as well as results obtained in scripts and instruments. It was observed in the case of risk for autism that cognition and language were more affected than in the case of non-autistic risk. In addition, the lack of creativity and dialogue during play allowed us to discuss the relationship between developmental delay and psychic suffering.